(untitled) (Revista Sistemas de Producción Agroecológicos, 2019)
This work evaluated the microbiological and physicochemical content of the leachate product of the banana rachis composting, coming from farms in three municipalities of Meta, Colombia: Granada, Fuente de Oro and Villavicencio. The characterization of fungi and bacteria was performed by microscopic examination, in which some of its structures were observed, additionally photographs were taken and later compared with what was reported in the literature, the genus of the microorganism was defined, taking into account the appearance of the colony. For the physicochemical characterization, multivariate analysis was performed using Pearson correlations, while the biodegradability of the leachate was evaluated using the Tukey test with a 95% reliability. An order Actinomycete bacteria was identified with four genera Clavibacter, Erwinia, Pseudomonas, Agrobacterium and five genera of fungi Fusarium, Aspergillium, Mucor, Rhizopus and Geomyces, distributed in the three locations with different frequency. In the physicochemical characterization of the leachate, according to the Tukey test there were no differences (P>0.05); the pH and total solids (ST) of the leachate, that is to say the suspended or sedimentable dissolved matter, varied between 8,3 and 17.666 mg/L for the materials of Fuente de Oro, and 8.9 and 18.882 mg/L for those of Villavicencio, presenting alkaline pH in all cases; in addition, there was a high alkalinity of the leachate that varied around 13.529 mg CaCO3/L for those of Fuente de Oro and 14100 mg CaCO3/L for those of Granada; on the other hand the turbidity of the samples varied between 130 NTU in Villavicencio materials and 231 NTU in those of Fuente de Oro; the potassium (K) contents of the leachate were high varying between 4.620 and 5.300 mg/L in Villavicencio and Granada respectively, indicating that the leachate from the three zones is not very biodegradable; according to Pearson’s correlations, leachates due to their high potassium content require a longer maturation time to reduce hardness and alkalinity, thus reducing the presence of bicarbonate, carbonate, magnesium and calcium ions in the samples. Pearson’s correlations indicated that the pH of leachate was positively correlated with the ST (r=0.99), alkalinity (r=0.94), iron (Fe) (r=0.93) and chemical oxygen demand (COD) (r=1.0); the pH was negatively correlated with turbidity (r=-0.99) and total hardness (r=-0.94). The leachates from Fuente de Oro and Granada were closer in terms of physicochemical characterization results, indicating greater biodegradability of them (30%), compared to those of Villavicencio (20%).